PERAN MAJELIS TAKLIM SEBAGAI PENDIDIKAN ALTERNATIF DALAM MEREVITALISASI PENGETAHUAN AGAMA (Studi Kasus di Majelis Ta'lim Al-Amanah) Desa Lubuk Ngin Kecamatan Selangit Kabupaten Musi Rawas) - Yesi Arikarani (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2017)
Majelis taklim is oldest education Islam, although not called majelis taklim. however, religious activity or religious education Islamic Prophet Muhammad SAW that took place by stealth at home friend Arkam bin Abil Arqam RA. And according to and according to now definition is majelis taklim held blatantly until flourish in other places openly. existence majelis taklim very important because was in middle of the communitywhich is one of three educational environment beside the family and the school. Relate revitalization needed for the resumption religious activities that previously may not have been implemented properly it now trying to improve the return programs majelis taklim. And this was reflected in history of the time of the Prophet in the began of the process of guidance is done through family environment He always made visits to each family in order to implement his treatise. The education Process through theoutside family environment only implemented after of Islamic syiar are widespread and rapidly growing Islamic civilization. And this is one example for us to can rebuild, increasing return activities or religious activity religious activities which had experienced ups and downs of people's interest in participating in religious activities.